Effect of Financial Development and Financial inclusion on Poverty Reduction in Nigeria - Okoduwa, Dorothy Ivie (Acta Universitatis Danubius. Œconomica, 2023)
This study investigated the effect of financial development and financial inclusion on poverty in Nigeria for the period 1981 to 2020. The study utilized causality and autoregressive distributed lag (ARDL) techniques. In the study financial development was proxy by tow indicators – banking sector development and stock market development. The results of the study indicated that banking sector development contributed significantly to poverty reduction in Nigeria while stock market development and financial inclusion had insignificant effect on poverty reduction in Nigeria. The causality results showed unidirectional causality from poverty to banking sector development and financial inclusion. The study concluded that the relationship between financial development and poverty reduction depends on the measurement of financial development. Hence, the study recommends the need for the banking sector to increase the volume of loan to the poor and ease constraints on credit accessibility to the poor. More so, operators of the stock market should develop special financial instruments such as SMEs Bond which will help to raise funds for SMEs and other small business units.